Influence of zeolitic structure on photoreduction property and hydrogen evolution reaction - Chatti, Ravikrishna V.; Dubey, Nidhi; Joshi, Meenal V.; Labhsetwar, Nitin K.; Joshi, P. N.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
A new photocatalytic material developed by supporting TiO(2) in combination with transition metal ion like cobalt and heteropolyacid (HPA) on the surface is facilitating enhanced photoreduction of water and methyl orange Zeolites being a solid acid play an important role in the electron transfer reaction, facilitated by the Lewis acid sites in the form of aluminium ions In the present work, four different zeolite matrices namely, NaY zeolite, ultrastable zeolite Y, beta zeolite and titanium silicate-1 have been used for the synthesis of new photocatalytic materials These materials have been evaluated for water splitting by an initial screening procedure using methyl orange photoreduction The photocatalyst containing Na Y has emerged as a potential photocatalyst with hydrogen evolution rate of 2730 mu mol/h/g of TiO(2) Hydrogen evolution was not observed for the composite photocatalysts synthesized using the other zeolite matrices It has been observed that physicochemical properties like Si/Al ratio, acidity and basicity of the zeolite support have a tremendous influence on the photoreduction property of these zeolite matrices (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: H(2) evolution; Lewis acidity; Si/Al ratio; water splitting; Zeolite structure

Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects